Community-based alternative breeding plans for indigenous sheep breeds in four agro-ecological zones of Ethiopia - Mirkena, T.; Duguma, G.; Willam, A.; Wurzinger, Maria; Haile, Aynalem; Rischkowsky, Barbara A.; Okeyo Mwai, Ally; Tibbo, Markos; Sölkner, Johann (Wiley, 2012)
Based on the results of participatory approaches to define traits in the breeding objectives, four scenarios of ram selection and ram use were compared via deterministic modelling of breeding plans for community-based sheep breeding programmes in four diverse agro-ecological regions of Ethiopia. The regions (and production systems) were Afar (pastoral/agro-pastoral), Bonga and Horro (both mixed crop-livestock) and Menz (sheep-barley). The schemes or scenarios differed in terms of selection intensity and duration of ram use. The predicted genetic gains per year in yearling weight (kilograms) were comparable across the schemes but differed among the breeds and ranged from 0.399 to 0.440 in Afar, 0.813 to 0.894 in Bonga, 0.850 to 0.940 in Horro, and 0.616 to 0.699 in Menz. The genetic gains per year in number of lambs born per ewe bred ranged from 0.009 to 0.010 in both Bonga and Horro. The predicted genetic gain in the proportion of lambs weaned per ewe joined was nearly comparable in all breeds ranging from 0.008 to 0.011. The genetic gain per year in milk yield of Afar breed was in the order of 0.018 to 0.020 kg, while the genetic gain per generation for greasy fleece weight (kg) ranged from 0.016 to 0.024 in Menz. Generally, strong selection and shorter duration of ram use for breeding were the preferred options. The expected genetic gains are satisfactory but largely rely on accurate and continuous pedigree and performance recording.